Quartz Solubility in the Two‐Phase Region of the NaCl‐H2O System: An Experimental Study With Application to the Piccard Hydrothermal Field, Mid‐Cayman Rise. (28th September 2018) - Scheuermann, Peter P.; Tan, Chunyang; Seyfried, William E.
Abstract: Hydrothermal experiments were performed at elevated temperature (420–500 °C) and pressure (31.0–51.0 MPa) in the NaCl‐H2 O system to measure quartz solubility in coexisting vapor and liquid and extend the calibrated range of the Si‐Cl geothermobarometer. In the vapor, the density‐based equations for quartz solubility of Fournier (1983, http://doi.org/10.1016/0016‐7037(83)90279‐X ) and Von Damm et al. (1991, http://doi.org/10.2475/ajs.291.10.977 ) agree well with the experimental data, while the equation of Fournier (1983) also accurately predicts SiO2(aq) concentrations in the liquid. Importantly, the equations of Fournier (1983) and Von Damm et al. (1991) were calibrated based on quartz solubility in single phase fluids (no coexisting vapor‐liquid) at higher pressure than investigated here. The new experimental data therefore extend the pressure range of the density‐equations and demonstrate that quartz solubility in either vapor or liquid can be treated independently as a function of temperature, pressure, and fluid density. The Si‐Cl geothermobarometer indicates that fluids venting from Piccard reach 540 ± 15 °C, 62.5 ± 3.0 MPa. These are the hottest and deepest conditions yet recorded by an actively venting seafloor hydrothermal fluid. Based on the calculated enthalpy differences between the subsurface fluid and that venting at the seafloor, approximately one third of the heat extracted at depth is lost during conductive cooling of the hydrothermal fluid. Incorporating the heat lost during conductive cooling into the overall budget at Piccard yields a flux of 100 ± 37 MW and an associated hydrothermal fluid flux of 1.2 ± 0.4 × 10 9 kg/year. The newly calibrated Si‐Cl geothermobarometer provides important constraints for accurate determination of heat and mass fluxes at axial vent sites. Key Points: Hydrothermal experiments were performed to extend the range of the Si‐Cl geothermobarometer Vent fluids at the Piccard hydrothermal field, Mid‐Cayman Rise, reach 540 °C, 62.5 MPa in the subsurface The Si‐Cl geothermobarometer provides important pressure‐temperature constraints to accurately calculate heat and mass fluxes